ORAL LICHEN PLANUS IN DRUG-RESISTANT PULMONARY TUBERCULOSIS PATIENT: A RARE CASE - Handayani, Rani; Erya Rahim, Siska; Nuriah Hikmawati, Virginia; Setiastuti, Hesti (Fakultas Kedokteran Gigi Unjani, 2024)
Drug-resistant pulmonary tuberculosis (DR-TB) is a hurdle in controlling pulmonary tuberculosis. The mucocutaneous tissues, including the oral mucosa, can be impacted by DR-TB medication, although infrequent. Highlighting Oral Lichen Planus (OLP) as a rare oral finding of drug side effects in DR-TB patients. Two male patients in DR-TB Clinic RSUD Tangerang City were referred to the Oral Medicine Clinic for complaints in the oral cavity. Treatment for DR-TB was given to the patient in months 8 and 11. The microscopic examination and sputum culture were negative when consulted. The patient denied any oral cavity complaints before being diagnosed with DR-TB. The intraoral clinical examination showed erosive lesions with a white keratinized plaque on the lips, buccal mucosa, labial mucosa, and tongue consistent with OLP. Pharmacological management involved using corticosteroids for mouthwash and lip ointment with responsive results. Scheduled oral hygiene was also planned to eliminate focus infection in the oral cavity. OLP is a chronic inflammation of the oral mucosa mediated by immunological mechanisms and triggered by various agents. Drugs are one of the known triggers of OLP lesions. The findings of side effects in the oral mucosa tissue are believed to be a result of the DR-TB regimen of these two patients. Long-term drug use triggers the development of OLP in patients with DR-TB. OLP is an oral mucosa finding of drug side effects that is rarely reported in DR-TB patients. DOI : 10.54052/jhds.v3n3.p317-332